Implementation of Deep Learning Through Meaningful, Mindful, And Joyful Learning in The Subject of Economics: a Case Study at State Senior High School 4 Sampit - Aulia Putri Aulia; M. Qahfi; M. Hadianur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
21st-century learning demands that students develop critical thinking skills, deeply understand concepts, and relate knowledge to real-life situations. However, learning practices in schools still tend to be teacher-centered, resulting in suboptimal student engagement. This study aims to analyze the implementation of in-depth learning (deep learning) through Meaningful Learning, Mindful Learning, and Joyful Learning in economics at SMA Negeri 4 Sampit and identify the obstacles faced in its implementation. The research used a qualitative approach with a case study design. The research informants consisted of two economics teachers and one vice principal for curriculum, who were selected randomly through purposive sampling. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña with validity tests through triangulation of sources and techniques. The results of the study indicate that the implementation of immersive learning has been applied at the planning, implementation, and evaluation stages of learning by linking material to real life, encouraging active student participation through discussions and presentations, and implementing assessments that pay attention to the learning process and outcomes. However, the implementation is not optimal due to teacher dominance, differences in student abilities, and unequal learning participation. This study shows that immersive learning has the potential to improve the quality of economics learning, but requires strengthening in the consistency of implementation and active student involvement.